2018
DOI: 10.4162/nrp.2018.12.3.243
|View full text |Cite
|
Sign up to set email alerts
|

Parents' meal choices for their children at fast food and family restaurants with different menu labeling presentations

Abstract: BACKGROUND/OBJECTIVESThis study examined the effect of nutrition labeling formats on parents' food choices for their children at different restaurant types.SUBJECTS/METHODSAn online survey was conducted with 1,980 parents of children aged 3–12 years. Participants were randomly assigned to fast food or family restaurant scenarios, and one of four menu stimuli conditions: no labeling, low-calorie symbol (symbol), numeric value (numeric), and both low-calorie symbol and numeric value (symbol + numeric). Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Accordingly, the use of nutrition information allows consumers to control their nutrient intake, which has a positive effect on public health [20]. The implementation of nutritional information has been studied widely in many types of restaurants [21][22][23][24][25][26][27][28].…”
Section: Introduction *mentioning
confidence: 99%
“…Accordingly, the use of nutrition information allows consumers to control their nutrient intake, which has a positive effect on public health [20]. The implementation of nutritional information has been studied widely in many types of restaurants [21][22][23][24][25][26][27][28].…”
Section: Introduction *mentioning
confidence: 99%
“…The heterogeneity of studies makes it difficult to compare findings. Differences in the settings of studies, such as a restaurant, cafeteria or fast-food outlet, may result in different findings (22) . Although early research regarding menu labelling with symbols showed a significant increase in healthy choices purchased (23)(24)(25)(26) , more recently, with a larger number of studies available, the research suggests that the use of symbols on menus is inconclusive (27) .…”
mentioning
confidence: 99%
“…Overall, the menu was designed to be like a realworld menu. This method has been used successfully in previous food choice research (12) . Prices were not indicated to avoid any undue influence.…”
Section: Instrumentsmentioning
confidence: 99%
“…However, these observations are more likely to be made in hypothetical scenarios than in observational studies (11) . One experimental study used a hypothetical menu scenario that asked parents to make selections for their children and found that labelling lowered the energy content of meals selected in a fast food restaurant but not a family restaurant (12) . Few papers have explored labelling strategies targeting children's meals in a full-service restaurant environment rather than a fast food restaurant.…”
mentioning
confidence: 99%